Leveraging affect: mobilizing enthusiasm and the co-production of the musical economy - Leyshon, Andrew; Thrift, Nigel; Crewe, Louise; French, Shaun; Webb, Peter (Taylor & Francis (Routledge), 2016)
This chapter considers the promises and problems of fandom and enthusiasm within capitalism, with particular reference to rise of crowdsourcing as a means of mobilising fan enthusiasm to fund new creative projects, with a particular focus on the music industry. Crowdfunding has emerged as an alternative way of funding projects caused by the more cautious investments of record companies, and is the latest development here firms and companies have sought to harness the affect and emotions of fans. However, although crowdfunding may tap new sources of money, the process is not without its costs, both in terms of the demands placed on its users and of being able to navigate a system that requires reserves of social, cultural and financial capital.